Digitalisasi Merketing Dan Optimalisasi Keuangan UMKM Pada Kelurahan Blitar Kecamatan Sukorejo Kota Blitar - Muchammad Nuruddin Islam; Ririt Iriani Sri S; Mohammad Wahed (LPPM Politeknik Pratama, 2023)
Marketing strategy is a form of a company's plan in the field of marketing to obtain optimal results. Information technology becomes an integral part of all fields, profit or non-profit. Education, banking, government, the arts, telecommunications, law, and tourism all use information technology in some capacity. MSMEs in the Blitar Village have problems in implementing digital marketing and financial optimization, so there is a need for solutions to these problems. The methods used are observation, interviews, focus group discussions, and demonstrations. The results of this activity are assistance in creating social media accounts, websites and market places and the delivery of material on the application of digital marketing such as the meaning of digital marketing, examples of digital marketing, the impact of digital marketing, and giving tutorial sessions on using e-commerce. And socialization was also held to optimize business finances. The response from the MSME players in the Blitar Village who were also the audience was very positive and they intend to learn to apply digital marketing and make business financial cash as soon as possible.